2022
DOI: 10.1002/adom.202200192
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interference Colors in Electrospun Microfibrous Mats

Abstract: The design of soft materials that change their optical properties in response to a variety of external stimuli is one step toward mimicking the dynamic color changing systems that are observed in nature. A simple, multiresponsive system is presented where the colors of core/sheath microfibers and microfibrous mats can be tuned by confinement (i.e., fiber diameter), temperature, and UV–vis irradiation. Microfibers are fabricated using coaxial electrospinning with a nematic liquid crystal core and a polymer shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…For example, using visual analysis of single PCL/LC-3 fibers under PLM, the blue start temperature was 36.9 ± 0.6 °C and the red end temperature was 32.0 ± 0.5 °C (compared to a blue start of 36.9 ± 0.5 °C and the red end temperature was 33.2 ± 0.4 °C for the fiber mats). The observed differences are relatively minor (Tables S7 and S8) and may be attributed to structural differences between individual fibers and bulk fiber mats as mats are anisotropic and made up of a range of fiber diameters (Table S3), which is known to affect the color of the fiber. , The transition temperatures using UV analysis were used for further analysis of the thermochromic properties of the fiber mats, i.e., color transitions using “color bandwidth” and “color play” values. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using visual analysis of single PCL/LC-3 fibers under PLM, the blue start temperature was 36.9 ± 0.6 °C and the red end temperature was 32.0 ± 0.5 °C (compared to a blue start of 36.9 ± 0.5 °C and the red end temperature was 33.2 ± 0.4 °C for the fiber mats). The observed differences are relatively minor (Tables S7 and S8) and may be attributed to structural differences between individual fibers and bulk fiber mats as mats are anisotropic and made up of a range of fiber diameters (Table S3), which is known to affect the color of the fiber. , The transition temperatures using UV analysis were used for further analysis of the thermochromic properties of the fiber mats, i.e., color transitions using “color bandwidth” and “color play” values. , …”
Section: Resultsmentioning
confidence: 99%
“…LCs have been successfully incorporated into polymer fibers via electrospinning. Coaxial electrospinning has been used to encapsulate LC in core–shell fiber cores. For example, nematic LCs such as MBBA, E7, 5CB, ,,,, mixtures of nematic LCs with a chiral dopant, and have been coaxially electrospun with a poly­(vinyl pyrrolidone) (PVP) shell. Cholesteric LCs have also been coaxially electrospun with a PVP shell and the individual fibers colored when viewed under polarized light microscopy, but the visible color of the fiber mat was not demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…After the electrospinning process, the uniform mesogens in the fiber show an interference color of yellow and UV cross-linking stabilized this orientation (Figure 5g,h). 58,59 With the increasing temperature, the interference color of the fiber gradually changed from yellow to blue, indicating the alignment of mesogens disturbed partially (Figure 5i). When the fiber entered the isotropic phase, the birefringence disappeared and the fiber slightly expanded as shown in Figure 5j.…”
Section: Model Of Uniform Electrospun Fibersmentioning
confidence: 99%
“…Liquid crystals, as versatile soft condensed matter, have been extensively utilized in the fields of display and sensing due to their exceptional responsivity to external stimuli. [13][14][15][16][17][18][19][20][21][22][23][24][25] In recent years, liquid crystals have garnered increasing attention and have been widely investigated in the realm of smart textiles. For example, Geng et al reported a CLC elastomer filament with reversible mechanically responsive colour variations, 26 and these CLC elastomer filaments can change from red to blue (a wavelength shift of 155 nm) when stretched up to 200%.…”
Section: Introductionmentioning
confidence: 99%